Nanostructured carbon nanotubes/copper phthalocyanine hybrid multilayers prepared using layer-by-layer self-assembly approach - Baba A. (2014)
In this report, we demonstrate a convenient method of fabricating single-walled carbon nanotubes/organic semiconductor hybrid ultrathin multilayers using a layer-by-layer self-assembly approach. Single-walled carbon nanotubes were solubilized by water-soluble cationic alcian blue pyridine variant and anionic copper phthalocyanine-3,4′,4″,4′″-tetrasulfonic acid tetrasodium salt, which were then utilized for electrostatic layer-by-layer multilayer fabrication. The solubilization ability of single-walled carbon nanotubes was studied in water by UV-vis absorption spectroscopy. The composites were highly dispersed owing to the π-π interactions. In situ surface plasmon resonance spectroscopy during the layer-by-layer multilayer fabrication indicated a stepwise increase in reflectivity, indicating the successive formation of nanostructured hybrid ultrathin films. Cyclic voltammetry revealed that the electroactivity of the hybrid film was enhanced by the incorporation of single-walled nanotubes. © 2009 Elsevier B.V. All rights reserved.